First report of an extended-spectrum β-lactamase-producing Raoultella ornithinolytica and a porin deficiency (OmpK35 absence) which was misidentified as Klebsiella oxytoca by an automated microbial identification system. Issue 1 (January 2016) - Zhang, Li-ping; Li, Xiao-hong; Xue, Wen-cheng; Meng, Dong-ya
Abstract : Raoultella ornithinolytica is an encapsulated Gram-negative aerobic bacillus belonging to the Enterobacteriaceae family. Originally it used to be a member of Klebsiella . However, in the year 2001, R. ornithinolytica was reclassified as a new genus type from the Klebsiella species along with two others, and this was based on new genetic approaches. Occurrence of Raoultella in human infections is rare, and its successful identification is confusing. We herein report a misidentification of R. ornithinolytica by the VITEK-2 Compact automatic microbial identification system (VITEK-2 AMS), but matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and 16S rRNA analysis could correctly identify it.